Nighttime banana consumption: A natural remedy for better sleep and blood pressure control in hypertensive patients - Abdullah, Ahmad Syafiq; Huda, Nor Aina Izzati; Faiz, Siti Safiah; Hafizuddin, Muhammad; Rahman, Nurul Aziz; Khalid, Amirul Faiz (Program Studi Keperawatan, Politeknik Negeri Subang, 2025)
Background: Hypertension is a significant global health concern, often linked with poor sleep quality, both of which contribute to increased cardiovascular risks. Dietary interventions rich in potassium, magnesium, and tryptophan have shown potential in improving blood pressure and sleep quality. However, the specific effects of nighttime banana consumption on these outcomes remain underexplored. Purpose: This study aims to investigate the impact of consuming bananas at night on blood pressure levels and sleep quality among hypertensive patients in the Health Community Kuantan, Malaysia. Methods: A randomized controlled trial was conducted with 120 hypertensive patients aged 30–65 years. Participants were randomized into two groups: the intervention group consumed one medium-sized banana (approximately 120 grams) one hour before bedtime daily for eight weeks, while the control group followed their usual diet. Blood pressure was measured weekly using an automated sphygmomanometer, and sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Statistical analyses, including paired t-tests and repeated-measures ANOVA, were performed to evaluate within- and between-group differences. Results: The intervention group demonstrated significant reductions in systolic (mean: 10.3 mmHg, p < 0.001) and diastolic (mean: 6.3 mmHg, p < 0.001) blood pressure compared to the control group. PSQI scores also improved significantly in the intervention group, with a mean reduction of 3.1 points (p < 0.001) from baseline, indicating enhanced sleep quality. The control group showed minimal changes in both parameters. Conclusion: Nighttime banana consumption is an effective, natural, and affordable intervention for improving blood pressure and sleep quality in hypertensive patients. These findings highlight the potential of whole-food dietary strategies as complementary therapies for managing hypertension and its associated conditions.